1997
DOI: 10.1051/aas:1997163
|View full text |Cite
|
Sign up to set email alerts
|

New “weak-line"–T Tauri stars in Lupus

Abstract: Abstract. We present first results obtained by a survey of the Lupus star forming region in search of new T Tauri stars. This study has been performed on the basis of deep pointed ROSAT observations in the Lupus dark clouds as well as data from the ROSAT All-Sky-Survey in the surrounding, less obscured regions. Our survey covers an area of about 230 square degrees, located between 15h 6 m and 16 h 24 m in right ascension and between −47• and −32• in declination. Identification of ROSAT All-Sky-Survey sources i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
113
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(121 citation statements)
references
References 16 publications
8
113
0
Order By: Relevance
“…Ophiuchus contains one of the nearest, best studied regions of star formation ; Lupus, like Taurus, appears to be forming only stars of low to intermediate mass, including more than 100 T Tauri stars recently discovered by Krautter et al (1997). Both clouds lie at similar distances (D150 pc) and have similar masses (D104 de Geus (1992) has shown that both lie near M _ ) ; the edge of an expanding H I shell surrounding the Upper Scorpius subgroup of the Sco-Cen OB association.…”
Section: First Quadrantmentioning
confidence: 99%
“…Ophiuchus contains one of the nearest, best studied regions of star formation ; Lupus, like Taurus, appears to be forming only stars of low to intermediate mass, including more than 100 T Tauri stars recently discovered by Krautter et al (1997). Both clouds lie at similar distances (D150 pc) and have similar masses (D104 de Geus (1992) has shown that both lie near M _ ) ; the edge of an expanding H I shell surrounding the Upper Scorpius subgroup of the Sco-Cen OB association.…”
Section: First Quadrantmentioning
confidence: 99%
“…Makarov (2007) linked the object kinematically to the Lupus association at a distance of approximately 185 pc. Henize (1976) and Krautter et al (1997) classified RXJ1615.3-3255 as a weakline T Tauri star, whereas Merín et al (2010) classified it as a potential transitional disc based on Spitzer spectra. resolved the disc at 880 µm with SMA observations and found that the emission from the disc is highly extended suggesting a large disc extending out to 115 au, and they measure a particularly low-density cavity extending to 30 au.…”
Section: Rxj16153-3255mentioning
confidence: 99%
“…ROSAT pre-main sequence stars in the area of the Lupus clouds Krautter et al (1997) report the discovery by the ROSAT X-ray satellite of an extended population of weak-lined T Tauri stars (WTTS) towards the Lupus clouds, which far exceeds in number the CTTS population coincident with the cloud cores. Some of these WTTS are seen projected onto regions of high obscuration, The thick solid and dashed lines are the 1 and 10 Myr isochrones, respectively, from the models by Baraffe et al (1998).…”
Section: Comparison To Other Populationsmentioning
confidence: 99%
“…Wichmann et al (1997b) argue that the age (up to 5−6 × 10 7 yr) and spatial distribution of the ROSAT stars are consistent with their belonging to the Gould Belt rather than to the Lupus clouds themselves, whose mean age is estimated to be around 5 Myr. The UCAC3 catalogue contains counterparts for 91 of the 136 ROSAT stars from Krautter et al (1997). These sources are, with a few exceptions, located in the same area as Group A in the vector-point diagram of Fig.…”
Section: Comparison To Other Populationsmentioning
confidence: 99%